A comprehensive study on a novel transcritical CO2 heat pump for simultaneous space heating and cooling – Concepts and initial performance. (1st September 2021) - Wang, Ji; Belusko, Martin; Liu, Ming; Semsarilar, Hesam; Liddle, Raymond; Alemu, Alemu; Evans, Michael; Zhao, Chunrong; Hudson, Julian; Bruno, Frank
Highlights: Detailed configuration of a CO2 heat pump with parallel compression is described. A complete CO2 system layout for simultaneous heating and cooling is presented. A validated mathematical model with FSD and VSD CO2 compressors has been developed. System performance of actual CO2 system is evaluated over three months of operation. Abstract: Carbon dioxide (CO2 ) is a natural substance and an environmentally benign, safe and economical refrigerant that can be used for cooling and heating systems. Unlike a traditional reversible heat pump system that only works either in heating or cooling, the air-to-air transcritical CO2 heat pump system reported in this paper is capable of providing simultaneous space heating and cooling through an Air Handling Unit (AHU) at any time. The system with cooling and heating capacities of 210 kW and 110 kW, respectively, was installed in a cinema complex in South Australia, and continuously operated from September to November in 2020. In this paper, the detailed configuration of the CO2 heat pump system with parallel compression is described. A complete system layout, comprising of cooling, heating and shared circuits, is revealed for the first time. A mathematical model based on highly efficient Bitzer compressors has also been developed in this study. The experimental data recorded in an entire heating period of approximately one hour has been utilised for model validation and analysis. Through the validation, the simulated power consumption for the compressors with Variable Speed Drive (VSD) and Fixed Speed Drive (FSD) has been compared to the experimental data with acceptable agreements. The simulated discharge temperatures agree with the actual temperatures measured within 10%. Moreover, the latest system performance from September to November has been evaluated based on the heating and cooling loads and combined COPs. It was found that the combined COP was relatively stable at around 3 regardless of climate conditions.